Influence of the acceptor roughness on the aspect ratio of silver paste lines printed by laser-induced forward transfer - Y. Chen; M. Morales; D. Munoz-Martin; C. Molpeceres (Results in Physics, 2016)
Silver paste voxels and lines are printed by laser-induced forward transfer onto three different substrates. Increasing the roughness of the acceptor substrates enhances the aspect ratio of the lines printed.